Multidimensional poverty reduction among countries in sub-Saharan Africa - Alkire, S; Jindra, C; Robles-Aguilar, G; Vaz, A (Oxford Poverty & Human Development Initiative (OPHI), 2017)
This paper focuses on changes in multidimensional poverty as measured by the global Multidimensional Poverty Index (global MPI) in Sub-Saharan Africa. Using data for 35 countries, we describe the changes in level, intensity, and composition of multidimensional poverty at the national level. For a subset of countries we discuss results at the subnational level and provide a brief comparison to changes in income poverty. Our findings suggest that 30 countries, home to 92% of the population in our sample, significantly reduced multidimensional poverty as measured by the global MPI for at least one comparison and significantly reduced the share of poor people. Looking within countries, we find different patterns of poverty reduction, with some countries reducing poverty for the poorest regions while poorer regions in other countries do not seem to benefit from the general reduction in poverty to the same extent. When comparing trends in income and multidimensional poverty reduction we find significant differences, indicating that a holistic approach to poverty reduction should look at both multidimensional and income poverty.